The Protective Activity of Kaempferol Glycosides from Soya Leaf Extract for Experimentally Induced Non-alcoholic Fatty Liver Disease in Wistar Rats - Y, Jyothi; S, Ajmal Sha; Kallepalli, Prasanthi; Samanta, Sairashmi; Gurung, Sushil; Mahato, Ankit Kumar; D R, Nishanth; Chettri, Rohit; Chhetri, Royan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Non-alcoholic fatty liver disease (NAFLD) ranks as one of the most important chronic liver conditions globally, characterized by excessive fat deposition in the liver, central obesity, insulin resistance and in general with characteristics of the metabolic syndrome. Thus, it is vital to treat NAFLD as well as its accompanying metabolic disorders. The present study is to evaluate Kaempferol glycosides activity from Glycine.max leaves extract in experimentally induced NAFLD in rats. The study evaluated the KG activity of G.max extract from leaves on a the HFD and Fructose induced rat model, utilizing Albino Wistar rats with daily doses of 200-250g. Parameters included body weight, liver weight, fasting blood glucose, fasting insulin, insulin resistance, lipid profiles, and histopathological investigations. The doses for KGE were 300mg/kg as medium and 400mg/kg as high. From the research results it was determined that medium dose (300mg/kg) and high dose (400mg/kg) demonstrated a substantial effect when compared to HFD and fructose induced positive control. The study demonstrated that Kaempferol glycosides from Glycine.max leaves extract can prevent and cure HFD and fructose-induced non-alcoholic fatty liver in Albino Wistar rats. The extract's action was substantial at medium and high doses, compared to HFD and fructose-induced positive controls. This shows that Kaempferol glycosides could be a promising natural therapeutic agent against NAFLD, hyperlipidaemic diseases, and metabolic syndromes with less adverse effects compared to conventional medications.